Minat Investasi Sebagai Pemediasi dalam Pengetahuan Investasi dan Perilaku Keuangan Terhadap Keputusan Investasi Mahasiswa Semarang - Kusuma Wardhani, Arrum Gusti; Widiastuti, C. Tri; Meiriyanti, Rita (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the effect of investment knowledge and financial behavior on investment decisions with investment interest as a moderating variable for students in Semarang City. This type of research uses quantitative research with a population of students in Semarang City. This study uses a purposive sampling technique with special criteria, because the number of students is unknown, the sample is determined by multiplying a minimum sample of 10 by the number of indicators 14 and 140 respondents are obtained. Measurements using a linkert scale which is then processed on SmartPLS 3.0 using the SEM-PLS method. The results show that investment knowledge has a significant positive effect and financial behavior does not have a significant effect on investment decisions. And investment interest as a moderating variable strengthens the influence of investment knowledge and financial behavior on investment decisions.